Trauma-Informed Educational Leadership in Formulating Student Protection Policies Post-Disaster - Fadilah Zahra; Benjamin Wils (PT Mutiara Bustan Ilmu, 2025)
This study explores the role of trauma-informed leadership in shaping protective policies for students in post-disaster contexts. Utilizing a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis involving school leaders, teachers, counselors, and students in disaster-affected areas. The findings reveal that school leaders play a critical role in adopting trauma-informed principles to ensure the creation of safe and supportive learning environments. These principles are reflected in the formulation of school policies aimed at safeguarding the psychosocial well-being of students who have experienced trauma. Despite challenges such as limited resources and systemic barriers, trauma-informed leadership enhances the effectiveness of protection policies and promotes a holistic recovery for affected students. The study contributes to the growing discourse on trauma-responsive education and offers practical implications for educational policymakers and practitioners in disaster-prone regions.